2010
DOI: 10.1200/jco.2009.26.2923
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II Study of Everolimus in Patients With Previously Treated Metastatic Gastric Cancer

Abstract: PURPOSE Everolimus, an oral inhibitor of the mammalian target of rapamycin, has shown antitumor activity in gastric cancer in preclinical and phase I studies. This phase II study evaluated the efficacy and safety of everolimus in pretreated patients with advanced gastric cancer. PATIENTS AND METHODS Patients with advanced gastric cancer who experienced progression despite prior chemotherapy received everolimus 10 mg orally daily until disease progression or study discontinuation. The primary end point was dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(118 citation statements)
references
References 31 publications
8
108
1
1
Order By: Relevance
“…[30][31][32] The mode of action of mTOR inhibitors 33 suggests that they may be associated with a direct impact on malignant cells and may also exert an antiangiogenesis effect, 34 as demonstrated in animal models. [35][36][37][38] A phase 3 trial of everolimus in patients with advanced renal cell carcinoma 39 and a series of phase 2 studies in patients with various other types of malignancies [40][41][42][43][44] have consistently demonstrated an antitumor effect of everolimus. Although the data remain preliminary, a series of uncontrolled trials have shown markedly lower rates of HCC recurrence after liver transplantation in patients receiving sirolimus-based immunosuppression versus a standard CNI regimen.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] The mode of action of mTOR inhibitors 33 suggests that they may be associated with a direct impact on malignant cells and may also exert an antiangiogenesis effect, 34 as demonstrated in animal models. [35][36][37][38] A phase 3 trial of everolimus in patients with advanced renal cell carcinoma 39 and a series of phase 2 studies in patients with various other types of malignancies [40][41][42][43][44] have consistently demonstrated an antitumor effect of everolimus. Although the data remain preliminary, a series of uncontrolled trials have shown markedly lower rates of HCC recurrence after liver transplantation in patients receiving sirolimus-based immunosuppression versus a standard CNI regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin and derivatives such as CCI-779 (temsirolimus, Torisel), RAD001 (everolimus), and AP23573 (ridaforolimus) act as cytostatic agents that slow down or arrest the growth of cells derived from several cancer types such as rhabdomyosarcoma (Hosoi et al 1999), prostate cancer (van der Poel et al 2003, breast cancer (Pang & Faber 2001), and Bcell lymphoma (Muthukkumar et al 1995). Early results from clinical trials reveal that they have antiproliferative activity in a subset of cancer, such as endometrial cancer (Oza et al 2011), pancreatic neuroendocrine tumors (Goldstein & Meyer 2011), gastric cancer (Doi et al 2010), and malignant glioma (Reardon et al 2011). However, only a subset of mTORC1 functions is sensitive to rapamycin treatment, hence the antiproliferative properties of this drug can be limited Choo et al 2008;Choo & Blenis 2009).…”
Section: Mtor Inhibitors and Therapeutic Significancementioning
confidence: 99%
“…Although everolimus in a phase II trial was demonstrated to be significantly beneficial clinically [32] , in a phase III trial, everolimus did not significantly improve OS for AGC after first-or second-line chemotherapy compared with BSC (GRANITE-1) [33] . The reason for these results was discussed to be partially attributable to the slightly higher percentage of placebo groups who initiated antineoplastic therapy after a study on drug discontinuation.…”
Section: Mtor Targeted Therapiesmentioning
confidence: 99%